1965
DOI: 10.1149/1.2423710
|View full text |Cite
|
Sign up to set email alerts
|

Potential of a Platinum Electrode at Low Partial Pressures of Hydrogen or Oxygen

Abstract: The open‐circuit potential on bright platinum in 1M H2SO4 was measured as a function of oxygen or hydrogen partial pressure from 10−2 to 10−7 atm. The very low rates of H2 or O2 flow which were required were produced by a special gas generator. Potentials predicted by the Nernst equation for the H+/H2 couple were not observed below 10−4 atm H2 partial pressure. A Nernst relation with a slope of 0.06 v/decade of oxygen partial pressure was found. The oxygen leak into the closed system used was found to be abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

1966
1966
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…As the redox concentration increases, the contribution of the redox half reactions increases and eventually dominates over the background half reactions. As far as we are aware, the only previous study that has observed a concentration dependent deviation from Nernstian behavior for molecules involves an inner-sphere electron transfer reaction, such as O 2 and H 2 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As the redox concentration increases, the contribution of the redox half reactions increases and eventually dominates over the background half reactions. As far as we are aware, the only previous study that has observed a concentration dependent deviation from Nernstian behavior for molecules involves an inner-sphere electron transfer reaction, such as O 2 and H 2 …”
mentioning
confidence: 99%
“…As far as we are aware, the only previous study that has observed a concentration dependent deviation from Nernstian behavior for molecules involves an inner-sphere electron transfer reaction, such as O 2 and H 2 . 13 ■ EXPERIMENTAL SECTION Electrode Fabrication. The electrodes used in this study were constructed by sealing either a 25 μm Pt wire (Alfa Aesar, 99.95% purity) into a borosilicate glass capillary (0.75 mm inner diameter and 1.5 mm outer diameter, Sutter Instrument) under vacuum.…”
mentioning
confidence: 99%
“…Dependence of currentless (stationary) potential of oxygen electrode on oxygen pressure (see (13)) was observed in solutions of various electrolytes: KOH [31], H 2 SO 4 [30,31,48], and HClO 4 [28,29]. This experimental fact indicates a single-electron character of reaction which defines the nature of currentless potential of platinum oxygen electrode.…”
Section: Discussion Of Orr Redox Cycle On Pt-electrodesmentioning
confidence: 99%
“…From repeated cathodic stripping determinations (3), the equivalent of about 3 or 4 monolayers of sorbed oxygen were detected. Rapid dissolution of oxygen in Pt was reported by Schuldiner and Warner (5), but this oxygen penetrated no further into the Pt surface than the first 2 or 3 atomic layers (5,6). The term "dermasorption" was suggested (5,6) to describe this form of occluded oxygen and to distinguish it from oxygen (known as absorbed oxygen) which had penetrated deeper into the metal lattice.…”
mentioning
confidence: 97%